The association of PON1 192 Q/R polymorphism and the risk of female infertility - Mashayekhi, F; Behrouzi, S; Yousefi, M; Salehi, Z (Cellular and Molecular Biology, 2015)
Infertility is a disease of the reproductive system defined by the failure to achieve a clinical pregnancy after 12 months of regular unprotected sexual intercourse. Both environmental and genetic factors are involved in female infertility. Paraoxonase (PON) is an oxidant enzyme which plays an important role in various diseases and is associated with inflammation, oxidative stress and lipid metabolism. The present study was aimed to evaluate the PON1 192 Q/R gene polymorphism in female infertility. Samples were obtained from 150 patients diagnosed with female infertility and 150 controls subjects and genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The PON genotype frequencies amongst the 70 cases were C/C=40%, C/T=52.8% and T/T=7.2%; the C and T allele frequencies were 66% and 34%, respectively. The PON genotype frequencies amongst the 73 controls were C/C=45.20%, C/T=50.70% and T/T=4.1%; the C and T allele frequencies were 70% and 30%, respectively. We observed a significant difference in the genotype distributions of PON1 192 Q/R polymorphism between patients and controls (P= 0.03). Our findings revealed that individuals with the variant QR had a significant decrease risk of female infertility (OR= 0.55, 95% CI= 0.33 – 0.91, P= 0.019). The data from this study indicates that the PON1 192 Q/R polymorphism may be associated with decreased risk of female infertility. Although more studies should be considered with larger number of patients and control subjects to confirm our results.